Empowering digital citizenship: An anti-cyberbullying intervention to increase children's intentions to intervene on behalf of the victim. (November 2020) - Vlaanderen, Anne; Bevelander, Kirsten E.; Kleemans, Mariska
Abstract: Cyberbullying rates among children are worrisome and the consequences of cyberbullying can be detrimental. Theory-based interventions to reduce cyberbullying are lacking. Therefore, this study examined whether an online anti-cyberbullying intervention based on the Theory of Planned Behavior could increase children's intention to intervene in cyberbullying incidents on behalf of the victim. An experiment ( N = 298, 10–12 years old) was conducted to investigate whether the intervention could positively affect the behavioral intention to intervene on behalf of the victim via changes in children's attitude, subjective norms, and perceived behavioral control. Results showed that children exposed to the anti-cyberbullying intervention had more intentions to intervene on behalf of the cyberbully victim compared to children who were exposed to a non-related intervention. However, no mediation effects were found for children's attitude, subjective norms, and perceived behavioral control. The effectiveness of the intervention in the current study shows that it is important to develop theory-based intervention programs that also focus on the role of bystanders. Highlights: A cyberbullying e-learning increased children's intention to intervene on behalf of a victim. Knowledge, awareness and empathy were positively affected by a cyberbullying e-learning. Contrary to the Theory of Planned Behavior, no mediation for subjective norms and perceived behavioral control was found. A cyberbully e-learning tool empowers children to stand up against cyberbullying. Incorporating the role of bystanders in cyberbullying research is of utmost importance.